Enhancement of Gas Production From Clayey Silt Hydrate Reservoirs Based on Near Wellbore Artificial Fractures Constructed Using High-Pressure Rotating Water Jets Technology - Li, Zhanzhao; Wan, Tinghui; Yu, Yanjiang; Liang, Qianyong; Lu, Hongfeng; Wang, Jingli; Tian, Lieyu; He, Huice; Li, Keliang; Qiu, Haijun (Frontiers in Earth Science, 2022)
Over 90% of the global hydrate resources are stored in very-low-permeability clayey silt reservoirs. The low permeability significantly restricts the efficiency of gas and water flow into the production well. To enhance gas production efficiency in low-permeability hydrate reservoirs, the high-pressure rotating water jets (HPRWJ) technology is proposed to construct near wellbore artificial fractures (NWAFs) in hydrate reservoirs. The HPRWJ avoid the risks of hydraulic fracturing as well as large-scale reservoir damage, which makes it more suitable for constructing fractures in hydrate-bearing sediments (HBS). In this article, the site SH7 in the South China Sea is studied to evaluate the feasibility of this technology for enhancing gas production of low-permeability hydrate reservoirs by numerical simulation. The results show that the gas productivity is increased by approximately three times by using the HPRWJ technology to construct NWAFs with a depth of 3 m. It is suggested that the proposed technology is a promising method for improving gas production from the low-permeability hydrate reservoirs. Furthermore, the gas production performance is closely related to NWAF depth, NWAF permeability, and NWAF spacing. For the site SH7 in the South China Sea, the NWAF depth, permeability, and spacing are recommended as 3 m, 3D, and 3 m, respectively.